Rational inattention in macroeconomics - Macaulay, A (2020)
In many markets, acquiring and processing the information needed to make optimal decisions costs agents time, effort, and/or money. This thesis is concerned with the macroeconomic implications of the way households behave in the face of these costs, which is known as rational inattention. The thesis consists of three self-contained chapters.